Heat shock proteins as potential biomarkers of heart failure - Yu. S. Timofeev; A. A. Afaunova; V. A. Metelskaya; A. A. Ivanova; O. N. Dzhioeva; O. M. Drapkina (Кардиоваскулярная терапия и профилактика)
The number of patients with heart failure (HF) has increased markedly over the past decades and continues to increase. During pathological cardiac remodeling in HF, vicious cycles of cellular stress are triggered. This review is devoted to a group of heat shock proteins (HSPs) stimulated by cellular stress, which make it possible to consider them as potential cardiovascular biomarkers, including for HF. The review presents the features of the most studied low-molecular-weight and high-molecular-weight HSPs, which can complement the range of non-invasive laboratory diagnostics and clinical data required when making a diagnosis. This will also help assessing the prognosis and choosing therapeutic strategy aimed at improving the patient's quality of life and reducing cardiovascular events in HF.The review aim is to analyze publications on biochemical studies of HSPs as diagnostic markers in HF patients.